THE UNIFYING POWER OF THE LOGOS In Memory of Professor Violeta Panzova (Annual of the Faculty of Philosophy in Skopje, 2020)
Everyone who has had the opportunity to experience the most valuableaspect of the educational process - that is, its influence on the shaping andflourishing of the human potential of the individual - seems to be able to capture,albeit intuitively, the deep, philosophical meaning of the term “teacher”.In this meaning, it refers not only to a professional, but also – or even primarily– to a spiritual category. A teacher is a person who, through words and deeds,reveals to us the true meaning of the lifelong activity of learning, understood asa process of self-development and self-actualization, as recognizing the uniqueontological “gift of the self” and nurturing it towards achieving its optimalform. It is a process based on the acquisition of knowledge of various kinds,but always inspired by the ethical pursuit of the good and aimed at establishinga delicate balance between one’s own and other persons’ perspectives.